Application of Nanoparticles in Tumour Targeted Drug Delivery and Vaccine - Tu, Yuhan; Yao, Zhiang; Yang, Wenjing; Tao, Shanhui; Li, Bin; Wang, Yun; Su, Zhijian; Li, Shijun (Frontiers in Nanotechnology, 2022)
Cancer is a major cause of death worldwide, and nearly 1 in 6 deaths each year is caused by cancer. Traditional cancer treatment strategies cannot completely solve cancer recurrence and metastasis. With the development of nanotechnology, the study of nanoparticles (NPs) has gradually become a hotspot of medical research. NPs have various advantages. NPs exploit the enhanced permeability and retention (EPR) of tumour cells to achieve targeted drug delivery and can be retained in tumours long-term. NPs can be used as a powerful design platform for vaccines as well as immunization enhancers. Liposomes, as organic nanomaterials, are widely used in the preparation of nanodrugs and vaccines. Currently, most of the anticancer drugs that have been approved and entered clinical practice are prepared from lipid materials. However, the current clinical conversion rate of NPs is still extremely low, and the transition of NPs from the laboratory to clinical practice is still a substantial challenge. In this paper, we review the in vivo targeted delivery methods, material characteristics of NPs and the application of NPs in vaccine preparation. The application of nanoliposomes is also emphasized. Furthermore, the challenges and limitations of NPs are briefly discussed.